Application for Handling Hybrid Grouper Eggs (Epinephelus lanceolatus x Epinephelus fuscoguttatus) - Muh Sulaiman Dadiono; Maheno Sri Widodo (Journal of Aquaculture Development and Environment, 2022)
Applications for handling hybrid grouper eggs (Epinephelus lanceolatus x Epinephelus fuscoguttatus) include the initial egg handling process, egg selection, egg counting and egg observation. The initial handling of hybrid grouper eggs (Epinephelus lanceolatus x Epinephelus fuscoguttatus) begins with stripping the female tiger grouper and male giant grouper to get eggs and sperm. Mixing eggs and sperm is done using chicken feathers. Egg selection is done to separate good and bad quality eggs. Good quality eggs will float on the surface, are round, transparent in color and have a core. Poor quality eggs will sink to the bottom and become milky white. The egg calculation technique uses the manual method with the help of a petri dish and a 20 ml beaker glass. Observation of eggs using a microscope magnification 40x. The fertilized egg has a transverse line between the nucleus of the egg which is a developing embryo. The unfertilized egg does not have a transverse line which indicates the egg does not have an embryo.